ANALISIS EFISIENSI PADA KOMPONEN SISTEM PEMBANGKIT LISTRIK TENAGA SURYA - Supri anto; Muhammad Fadlan Siregar (Universitas Medan Area, 2020)
Efficiencies in the components of solar power generation systems (PLTS) are things that need to be known for an effective system design. The research of efficiency analysis on the components of solar power generation systems aims to determine the efficiency of PLTS system components, namely the efficiency of the solar charge controller (SCC), the efficiency of the inverter and the efficiency of the conduit between the battery and the inverter. The method used is an experimental method that designing a solar home system and measuring the quantity of electricity in each component of the system. The equipment used is a 2000 wp capacity solar panel, a 3000 watt inverter, a 60 ampere solar charge controller and a 400 Ah 24 volt battery. The results showed that the average solar charge controller efficiency was 80%, power losses of 20% occurred due to the limitation of the voltage and current at the SCC output to protect the battery from overvoltages and currents from the photovoltaic module. The results of the research show that the power wasted due to the protection of this SCC varies from 32 watts to 239 watts on the photovoltaic input power of 149 watts to 1239 watts. The average efficiency of an inverter is 84% and fluctuates from 71% to 97%, 71% efficiency occurs at a load of 38 watts while for an efficiency of 97% occurs at a loading of 277 watts. The average cable efficiency is 96% with fluctuations in cable efficiency because loading only 2% and This fluctuation is more stable than the fluctuation of the efficiency of the inverter and SCC, which is 26% each